Treatment options for postmenopausal osteoporosis - Walsh GM (Dove Medical Press, 2012)
Garry M WalshDivision of Applied Medicine, School of Medicine and Dentistry, Institute of Medical Sciences, University of Aberdeen, United KingdomTo serve our readership better, future editions of Therapeutics and Clinical Risk Management will once again feature the Editor’s comments and views on some of the articles published in that issue of the journal.Bone is a complex tissue that, in addition to protecting vital organs and giving mechanical support for muscles and joints, provides a mineral reservoir essential for calcium homeostasis, together with the microenvironment essential for hematopoiesis. Osteoporosis is the most common metabolic bone disease, with up to a third of postmenopausal women suffering from this increasingly important public health problem. Key characteristics include low bone mineral density with microarchitectural deterioration of bone tissue leading to increased susceptibility to fragility fractures.